2004
DOI: 10.2304/ciec.2004.5.2.6
|View full text |Cite
|
Sign up to set email alerts
|

Child-Rearing Practices in a Selected Sample of Parents with Children in Childcare in Singapore

Abstract: This article reports on a study based on interviews with 40 parents in Singapore. The study examined parents' views about their children's development and learning, and how these were or were not congruent with the views and practices of the childcare centre the children were attending. Findings showed that, although there were some similarities, there was a great variety of differences between practices at home and at the centre. Differences were apparent in discipline and expected levels of self-help skills.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 18 publications
0
21
0
1
Order By: Relevance
“…The emphasis is clearly on the pursuit and attainment of educational qualifications. Employment of private tutors, even during the early years, as seen from Ebbeck & Gokhale's (2004) study, reflects both a significant capacity to pay for, and the importance attached to, education. As Rodan claims, '[t]here is probably no other place in the world where formal qualifications represent as much economic or social capital ' (1996, p. 24).…”
Section: The New Preschool Curriculum Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…The emphasis is clearly on the pursuit and attainment of educational qualifications. Employment of private tutors, even during the early years, as seen from Ebbeck & Gokhale's (2004) study, reflects both a significant capacity to pay for, and the importance attached to, education. As Rodan claims, '[t]here is probably no other place in the world where formal qualifications represent as much economic or social capital ' (1996, p. 24).…”
Section: The New Preschool Curriculum Frameworkmentioning
confidence: 99%
“…This is especially so in Singapore, where education is very much dependent on a market-led economy, and parents' educational aspirations have a major influence on the type of preschool programme their children receive (Sharpe, 2000;Sharpe & Gan, 2000;Fan-Eng & Sharpe, 2000). In Singapore, it is not unusual for parents to prepare their children for the academic rigours of the primary school system, and provide them with some form of early education to give them a head start (Sharpe, 2000;Ebbeck & Gokhale, 2004). Tan-Niam, for instance, argues that in Singapore, 'parents favour preschools with an emphasis on academic skills', as reflected in the highly structured curriculum (Tan-Niam, 2000, p. 140), and this is mainly because parents perceive it to be essential to prepare their children for entry into the school system.…”
Section: The New Preschool Curriculum Frameworkmentioning
confidence: 99%
“…Their concerns is to see children have a clear understanding of boundaries and misbehavior and their consequences if consistent behavior and correcting strategies are not enforced by domestic helpers versus by parents. Ebbeck and Gokhale (2004) found that 87% of risk behavior group were boys from homes where the mother was absent during childhood, compared to only 13% for the comparison group. In addition, 81% of mothers of boys in the study group reported little contact with their children during childhood, compared to 19% of mothers in the comparison group.…”
Section: Mother-absencementioning
confidence: 93%
“…To some extent, there are likely to seek for the children's cooperation rather than playing a role in teaching or disciplining them (Ip et al, 2008). In the study conducted in Singapore, Ebbeck and Gokhale (2004) found that majority of the parents surveyed do not expect the house helper as being one of the disciplining, despite the amount spent with children compared to the parents in caring the children. Their concerns is to see children have a clear understanding of boundaries and misbehavior and their consequences if consistent behavior and correcting strategies are not enforced by domestic helpers versus by parents.…”
Section: Mother-absencementioning
confidence: 99%
“…Moreover, as the relationship between play and learning is not always apparent, parents and even preschool educators are not fully convinced on the educational value of a play-based approach to learning. In an interview survey of 40 Singaporean parents, Ebbeck and Gokhale (2004) found that many parents sent their children for private tuition in their final preschool year as they were not confident that a curriculum adopting an informal, interactive format of teaching and learning would adequately prepare their children for formal schooling.…”
Section: Use Numbers In Daily Experiencesmentioning
confidence: 99%